PONDOK PESANTREN AS'ADIYAH - Muhammad As'ad (Al-Qalam, 2009)
This article is the summary of research on the oldest boarding school inSouth Sulawesi : As 'adiyah. It aims to describe its religious view, lecture,learning system, networks and relation with society.Result shows that As'adiyah boarding school embraces Ahlusunnahwal Jamaah based on Imam Syafi' teachings. It can be categorized, as"moderate group " applying tawazun and tasamuh principles to solvereligious issues.It is the oldest and parent boarding school where the alumni have alsobuilt many other boarding schools in other areas and formed a vastnetwork. The relationship between them is not formal but emotional,mainly based on its religious system and views. The network is not onlylimited to its own branch, but also to DDI's and to those developed by itsalumni and strengthened by the establishment of As'adiyah and DDIboth as formal religious and social organisations.The network with other boarding schools, communities and other institutionsis much depended on its leader (kiyai) as a center of all theiractivities. His charisma and popularity is the main factor in increasingthe popularity of, mainly among primordial community, and their interestto the boarding school.